(untitled) (International Seven Journal of Health Research, 2023)
Introduction: Intrauterine Growth Restriction is defined as the inability of the fetus to reach its growth potential and can be caused by maternal, placental and fetal factors. Objective: The study aims to make a major social contribution, in order to help the health sectors develop actions aimed at improving the quality of life of pregnant women, promoting changes in behaviors that are harmful to the fetus and thus contributing to reducing infant morbidity and mortality. Methodology: A bibliographic survey was carried out in the Scielo, PubMed and VHL databases, between 2010-2020, with the descriptors and their combinations in Portuguese and English, using the Boolean operators: "fetal growth retardation" OR "intrauterine growth retardation" OR "intrauterine growth restriction" AND "risk factors" AND "intrauterine growth restriction" AND "Brazil". After applying inclusion and exclusion criteria, 10 articles were selected. Results: Analysis of the articles showed that Intrauterine Growth Restriction is strictly related to five themes: evolution in prenatal treatment; socioeconomic factor; low birth weight; fetal mortality and serum leptin concentration, eclampsia and HIV. Conclusion: The analyses available on the main categories related to IUGR showed that lack of prenatal care, poor socioeconomic situation, low leptin concentration during pregnancy, pre-eclampsia and viral infections such as HIV are risk factors for IUGR in Brazil.